Internet for information services - Nair, R. Raman (Ess Ess Publications, 2002)
Contents of material: 1/ Introduction. 2/ Network basics. 3/ TCP/IP fundamentals. 4/ Unix familiarisation. 5/ Gopher for information search. 6/ Usenet for current news. 7/ Telnet and electronic libraties. 8/ FIP for document retrieval. 9/ WAIS and catalogue search. 10/ Scientific communication. 12/ World Wide Web through Unix. 13/ Libraries in cyberspace. 14/ Puting library internet. 15/ Basics of HTML. 16/ Internet tomorrow.